KONSTRUKSI PEMBENTUKAN KARAKTER PADA KELUARGA SUKHINAH DI GRAHA PASEK BANJAR KAJA KELURAHAN SESETAN KECAMATAN DENPASAR SELATAN KOTA DENPASAR - Ni Made Surawati; Ida Ayu Putu Sari; A.A Ketut Raka (UNHI PRESS, 2021)
The family is the first and foremost place of education for children. However, due to the influence of globalization and modernization, the phenomenon of materialistic and consumerist lifestyles has emerged, so that true happiness is measured by material (artha). Such a lifestyle can certainly cause a shift in the meaning of the family, such as the rise of divorce rates, family disorganization, lack of parental attention to children, domestic violence, MBA, and degradation of the younger generation. It is feared that people's lives can cause the values ​​of social wisdom, spiritual values, and the duties of parents in building character in children to be neglected. Related to that, there is a family phenomenon in the city of Denpasar, namely the Graha Pasek family which is thought to be able to educate good character in their sons, and is suspected of being able to maintain the value of harmony between other family members, so that researchers are interested in conducting a deeper study of